PENGARUH JUS BUAH TOMAT TERHADAP KADAR HEMOGLOBIN PADA SISWI MENSTRUASI DI SMA SULTAN AGUNG 02 KALINYAMAT - Maulida Calvina Elsandro,; Indanah, Indanah; Tri Suwarto, (Nusantara Hasana Journal, 2025)
A person is said to have anemia if in women aged over 15 years but not pregnant normally 12 g / dL, said to have mild anemia if 11.0-11.9 g / dL, moderate anemia if 8.0-10.9 g / dL and severe anemia if less than 8.0 g / dL. To find out the Hb levels in female students at SMA Sultan Agung 02 Kalinyamat, a check will be carried out using a hymoglycometer tool which was carried out at the beginning of the study and the end of the study. The average hemoglobin level in menstruating female students at SMA Sultan Agung 02 Kalinyamat before giving Fe tablets was 15.0 g / dL and after giving Fe tablets was 16.3 g / dL. The average hemoglobin level of menstruating female students at SMA Sultan Agung 02 Kalinyamat before giving tomato juice and Fe tablets was 14.0 g / dL and after giving tomato juice and Fe tablets was 15.8 g / dL. There was a difference in the average hemoglobin levels in the intervention group before and after administration of tomato juice (JUBETA) with a p-value of 0.256 (α: 0.05) at Sultan Agung 02 Kalinyamat High School. There was a difference in the average hemoglobin levels in the control group before and after administration of Fe tablets p-value of 0.257 (α: 0.05) at Sultan Agung 02 Kalinyamat High School. There was no significant difference in the average increase in hemoglobin levels in the intervention group and the control group p-value of 0.256 (α: 0.05) at Sultan Agung 02 Kalinyamat High School.